Association between total genotype score and muscle injuries in top-level football players: a pilot study - Massidda, M.; Flore, L.; Cugia, P.; Piras, F.; Scorcu, M.; Kikuchi, N.; Cieszczyk, P.; Maciejewska-Skrendo, A.; Tocco, F.; Calò, C. M. (Sports Medicine - Open, 2024)
Background Recently, genetic predisposition to injury has become a popular area of research and the association between a few single nucleotide polymorphisms (SNPs) and the susceptibility to develop musculoskeletal injuries has been shown. This pilot study aimed to investigate the combined effect of common gene polymorphisms previously associated with muscle injuries in Italian soccer players.